Masters of Healing: Cocaine and the Ideal of the Victorian Medical Man. (2nd January 2016) - Small, Douglas
Abstract : This article offers a new perspective on the relationship between cocaine and medical practitioners in late nineteenth- and early twentieth-century Britain. Cocaine is often understood as one of a number of potentially addictive substances to which Victorian physicians and surgeons were regularly exposed, and tempted to indulge in. However, while cocaine has frequently been associated with discourses of addiction, this article proposes that it was also widely represented as a technological triumph, and that the drug was frequently used as a symbol for the scientific and moral virtues of the medical man. The argument draws on popular journalism, medical publications, and fiction to establish the cultural context of cocaine at the fin de siècle . In 1884, cocaine was revealed to be the first effective local anaesthetic, and this article traces the processes by which cocaine came to be regarded as the iconic achievement of nineteenth-century therapeutic science. This aura of innovative brilliance in turn communicated itself to the medical professionals who employed cocaine in their work, so that many patients and practitioners alike depicted cocaine as a most fitting emblem for the idealized selfhood of the modern medical man. This idea also informs portrayals of the drug in fiction, and I conclude with a detailed analysis of L. T. Meade's 1895 short story, 'The Red Bracelet' (published in the Strand Magazine as part of Meade's series, 'Stories from the Diary of a Doctor'), as an example of the way in which cocaine functions as metaphor for the physician's unassailable moral primacy and technical excellence.